Frailty: mind the gap. (29th December 2017) - Mudge, Alison M; Hubbard, Ruth E
Abstract: Frailty has become the focus of considerable research interest and media attention over the past 15 years. While it has much to offer geriatric medicine, potential pitfalls also need to be acknowledged. The conceptualisation of frailty in very different ways—as a syndrome or a risk state—has created semantic dissonance: the frailest patients by one definition may have early sarcopenia, by another be bedbound and in institutional care. Caution is required in transferring findings between studies enroling these different populations. Furthermore, a yawning gap has emerged between the number of studies reporting the associations of frailty and those investigating interventions such that the empirical benefits of identifying and treating frailty currently remain unclear. Perhaps most importantly, frailty research has evolved with little account of the perspectives and preferences of patients themselves. The label of 'frail', being linked to mental or moral weakness, has pejorative implications and care should be taken to avoid the adverse functional effects of negative priming. Here, we suggest pathways for future studies to provide a stronger evidence base to apply this important concept. This research is essential to avoid frailty becoming the new cloak of ageism, a tool for discrimination and disempowerment applied to the most vulnerable.